Rancang Bangun Sistem Informasi Manajemen Pengarsipan Dokumen Sertifikasi Guru pada Kementerian Agama Kabupaten Nagekeo Menggunakan Metode Extreme Programming (XP) - Dia Auliani; Asrul Azhari Muin; Syahbudin Syahbudin (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2026)
Previously, teacher certification document management at the Ministry of Religious Affairs in Nagekeo Regency was conducted manually, which complicated data retrieval, grouping, and verification processes. These limitations often led to inefficiencies, delays, and difficulties in ensuring data accuracy and completeness. In response to these challenges, a teacher certification document archiving management information system was designed and developed using the Extreme Programming (XP) method, which emphasizes collaboration, flexibility, and iterative system development. This system provides integrated features, including document upload, storage, verification, and recapitulation, which support the smooth administration of allowance disbursement and audit requirements. By integrating these processes into a single platform, the system helps reduce errors and improves overall workflow efficiency. The results showed that the implementation of this system significantly improved the efficiency and accuracy of document management. Furthermore, the System Usability Scale (SUS) test yielded a score of 72.97, which falls into the Acceptable category, indicating that the system is suitable for use by both teachers and administrators. Overall, this system serves not only as an archiving tool but also as a practical technological solution that simplifies and enhances the document management process.